2011
DOI: 10.1119/1.3543586
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic (and Simple!) Demonstration of Newton's Third Law

Abstract: An operational understanding of Newton's third law is often elusive for students. Typical examples of this concept are given for contact forces that are closer to the students' everyday experience. While this is a good thing in general, the reaction force can sometimes be taken for granted, and the students can miss the opportunity to really think about what is going on. In the case of magnetic forces, however, the notion of action at a distance actually requires a careful inspection of the forces involved and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…They can feel the force of 'resistance' (as a reaction) upon pulling the rope one end of which was tied to a window. The findings of this research regarding the contributions of demonstrations to learning reinforce finding that demonstration is a remarkably simple but strikingly effective approaching requiring the use of specialized equipment (Feldman, 2011).…”
Section: Results For the Third Yearsupporting
confidence: 73%
See 1 more Smart Citation
“…They can feel the force of 'resistance' (as a reaction) upon pulling the rope one end of which was tied to a window. The findings of this research regarding the contributions of demonstrations to learning reinforce finding that demonstration is a remarkably simple but strikingly effective approaching requiring the use of specialized equipment (Feldman, 2011).…”
Section: Results For the Third Yearsupporting
confidence: 73%
“…Other research found junior secondary school students, senior high school and university students to experience difficulty when distinguishing between interaction and balance forces (Zhou et al, 2015). In Feldman's (2011) work, a simple demonstration of NTL is presented in the context of a magnet falling through a hollow conducting tube. The results are unambiguous and lead students to an irrefutable verification of NTL.…”
Section: Introductionmentioning
confidence: 99%
“…More and more, classical bar magnets give place to modern technological solutions. Strong and robust neodymium magnets contribute to fresh educational innovations [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Penguasaan konsep Fisika Dasar sebagai sesuatu yang terkait dengan materi fisika sebelumnya bukan dari salah satu atau konsep fisika yang baru (Ingerman & Booth, 2000). Hasil penelitian Yuruk, Beeth, & Andersen, 2009;Shaw, 2012;Stocklmayer, Rayner, & Gore, 2012;Feldman, 2011;Terzella, et.al., 2008;Portillo-Velez, et.al., 2013 menunjukkan bahwa memahami konsep fisika dengan pemikiran konsep yang sederhana. Berbagai upaya telah ditemupuh untuk menyajikan pembelajaran yang meminimalisir kesalahan konsep Fisika (Budhi, 2018).…”
unclassified